Inclusive Educational Environment: Interaction of Teachers and Professionals of an Educational Organization - Sunko, T.Y. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2020)
The article is devoted to the pilot study of the problem of professional interaction in inclusive educational environment. The components of the development of an inclusive environment in education are highlighted. The purpose of the study is defined as studying the characteristics of the interaction between teachers of various levels of education in the work with students with disabilities in an inclusive educational environment. The results of an empirical study of online sample of volunteers (N=64) are presented. Respondents answered to the questionnaire about their attitude to the idea of inclusion, difficulties in interaction, the forms of interaction used and their willingness to request help. The results of the study based on a conventional content analysis, showed that interaction in an inclusive educational environment is built mainly through consultations (75%), workshops (59,4%) and other forms, while complicating professional interaction among more than half of respondents, mainly, the uncertainty of the responsibility of specialists in psychological and pedagogical support and various difficulties in building relationships. The data obtained show rather a different attitude towards the idea of inclusion in education in the light of the development of the inclusive educational environment of the educational organization, which determines the choice of the forms of interaction used. Статья посвящена пилотному исследованию проблемы профессионального взаимодействия в инклюзивной образовательной среде. Выделены компоненты развития инклюзивной среды в образовании. Определена цель исследования: изучение особенностей взаимодействия педагогических работников различных уровней образования при работе с обучающимися с ограниченными возможностями здоровья и инвалидностью в инклюзивной образовательной среде. Представлены результаты эмпирического исследования, проведенного в онлайн формате на выборке добровольцев (N=64). Респонденты отвечали на вопросы анкеты об отношении к идее инклюзии, затруднениях во взаимодействии друг с другом, об используемых формах взаимодействия и готовности при этом запрашивать помощь. На основе конвенционального контент-анализа данных было показано, что в инклюзивной образовательной среде взаимодействие выстраивается преимущественно через консилиумы (75%), семинары-практикумы (59,4%) и другие формы. При этом осложняют профессиональное взаимодействие, по мнению большей части респондентов, в основном неопределенность круга ответственности специалистов и различные затруднения в выстраивании взаимоотношений с педагогами. Полученные данные свидетельствуют об отсутствии консолидированного мнения об идее инклюзии в образовании, что определяет особенности взаимодействия педагогических работников в инклюзивной образовательной среде.